Methodology for Determining the Halal of Medicinal and Food Products in Maslahah Perspective - Muhammad Nusran; Abdul Muher; Sitnah A. Marasabessy; Nurlaila Abdullah (JASNA : Journal For Aswaja Studies, 2021)
AbstractMedicine  and  food  are  the  two  primary  commodities  needed  for  humans.  Both  are  very  important  for maintaining  human survival  and  also  the  environment.  With  the  rapid  development  of  science  and technology  (saintec),  including  the  production  of  food  and  medicine,  there  have  been  many  product innovations that utilize natural resources optimally or reprocess existing resources. It is undeniable that advances in science and technology are able to produce various products that not only make optimal use of resources, but are able to answer the various human needs for medicine and food. With the obligation, especially Muslim consumers, to only consume Halal medicines and foods, problems arise related to the halal status of medicinal and food products. Even though there have been many  writings from  scholars regarding the methodology of stipulating halal law or the prohibition of something, it will be, but with the phenomenon of the very wide variety of medicinal and food industry products, this methodology is still very important  to  be  reviewed  again.  The  aim  of  this  paper  is  to  produce  a  specific  methodology  for  the determination of halal medicinal and food products from a Maslahah perspective. This paper is a literature study  using an analysis of the  istimbath process using the  Maslahah perspective  on medicinal and food products.The  results  of  this  study  are  a  methodology  that  canbe  used  as  a  basis  for  determining  the halalness of medicinal and food products from the Maslahah perspective as well as practical instructions for non-Sharia communities to assess whether a product is Halal or not.Keywords: Halal, medicine, food, istimbath, maslahah, methodology